Guns, violence, politics: the gyre widens - Garen J. Wintemute (BMC, 2021)
Abstract Inter-related sustained upward trends in firearm purchasing, violence, and political extremism are converging to put the USA at risk for disaster and threaten our future as a democracy. This narrative review provides a critical assessment and call to action. It explores each trend separately, considers the effects of their likely and imminent convergence, and suggests possibilities for collective and individual action to prevent or at least reduce those effects.